Perspectivas éticas, vieses taxonômicos e valor instrumental das espécies: uma análise histórica e conceitual em biologia da conservação - Valente, Cristiele Barbosa (2018)
Since the 1960s, Conservation Biology (CB) has aimed to understand the causes and predict the consequences of biodiversity loss and then recommend conservation actions. The choice of taxa studied and the recommendation for their conservation is partly determined by the ethical and moral values of the research groups, what we call the ethical perspective. According to the biocentric perspective, species should be conserved because they have intrinsic value, derived from the right to exist, independent of human well-being. For the anthropocentric perspective, conservation should be based on the benefits that species generate for humans. Since the 1990s, the anthropocentric approach to ecosystem services has been consolidated, advocating the attribution of value to species and the prioritization of conservation based on this. To define these values, we need to understand the functional role of species in communities because this determines the services. Therefore, to understand how ethical aspects have been influencing conservation recommendations, we need to evaluate in an integrated way the ethical vision and preference for taxonomic groups in CB research, as well as integrate concepts from economics and ecology to understand the relationship between the functionality and economic value of species. Our results show that the biocentric perspective is predominant in CB. Most authors do not explicitly justify conservation because the conservation of targets seems unquestionable. We also observed a growing bias that favors studies of animals over plants and, among animals, vertebrates over invertebrates. These biases are increasing, thus reinforcing investment in the conservation of more charismatic taxa. We assess how local extinction affects the economic value of remaining species in different scenarios of functional redundancy. Using examples, we demonstrate how the economic value of species associated with their contributions to ecosystem services can vary under different scenarios of extinction and loss of ecological functions.